2003
DOI: 10.1007/s00125-003-1126-4
|View full text |Cite
|
Sign up to set email alerts
|

Gly972Arg variant in the insulin receptor substrate-1 gene and association with Type 2 diabetes: a meta-analysis of 27 studies

Abstract: Aims/hypothesis. Several case-control studies have examined the association between the Gly972Arg variant in the IRS-1 gene and Type 2 diabetes, but most had limited power and results could therefore be conflicting. Methods. We systematically reviewed the literature by means of a meta-analysis and investigated sources of heterogeneity in results of different studies.Results. The summary risk ratio, based on 3408 cases and 5419 control cases from 27 studies, was 1.25 (95% CI 1.05-1.48). The results, however, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 54 publications
5
102
2
6
Order By: Relevance
“…Previous studies of genetic risk factors for the development of Type 2 diabetes with complex polygenic inheritance have shown that the effect of a single genetic variant, measured as relative risk, is likely to be in the range of 1.25 to 1.5 [22,23,24,25]. In the present case-control study we have a high statistical power (>95%) to detect a relative risk of 1.25, and thus it seems unlikely that variation of the INS-VNTR as estimated by genotyping the −23 HphI SNP represents a major risk factor in the pathogenesis of Type 2 diabetes among Danish Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of genetic risk factors for the development of Type 2 diabetes with complex polygenic inheritance have shown that the effect of a single genetic variant, measured as relative risk, is likely to be in the range of 1.25 to 1.5 [22,23,24,25]. In the present case-control study we have a high statistical power (>95%) to detect a relative risk of 1.25, and thus it seems unlikely that variation of the INS-VNTR as estimated by genotyping the −23 HphI SNP represents a major risk factor in the pathogenesis of Type 2 diabetes among Danish Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Having been unable to reproduce the specific association of G972R with type 2 diabetes suggested by Jellema et al [6], we wondered whether other nearby variants (in LD with G972R in some samples but not in others) might account for the association signal noted by other groups. Our study design was well powered to detect associations with similar allele frequencies and putative GRR as proposed for G972R; in addition, its ability to capture common variants in the region was reasonably comprehensive.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, the common missense variant glycine → arginine at codon 972 (G972R) [5] was associated with type 2 diabetes in a meta-analysis of 27 studies comprising 8,827 subjects, although the statistical significance of this result was modest [6]. To test the reproducibility of this association, we recently attempted to replicate the same genetic model in large samples totalling 9,000 white individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies found that the IRS-1 G972R variant is associated with insulin resistance [25,28,56], body fat distribution [27], type II diabetes [28], hyperlipidemia, and coronary artery disease [29][30][31]. Other studies, however, have not confirmed these findings [50,[57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 93%
“…IRS-1 has an essential mediating role in apoptosis, cell differentiation, and cell transformation through its activity in these pathways [23,24]. A common variant in the IRS-1 gene results in an amino acid change at codon 972 (G972R) that has been associated with impaired insulin signaling [25], obesity [26], body fat distribution [27], type II diabetes [28], hyperlipidemia, and coronary artery disease [29][30][31]. In vitro assays suggest the missense variant changes the ability of the molecule to bind the p85 subunit of PI3-kinase, but does not alter IRS-1 protein expression levels [32].…”
Section: Introductionmentioning
confidence: 99%